The American Strategy in the Middle East (Objectives - Pillars - Mechanisms) - Marjiya Ibrahim Mohammed,; Amna Abdul Rahman Warith, (Journal of Scientific and Human Dimensions, 2026)
Since its emergence as a central actor in international conflict, the United States of America has played a decisive role in structuring regional power balances in the Middle East in accordance with its strategic interests. Within this framework, Iraq was regarded as both a strategic and economic challenge to U.S. national security, prompting policies that led to the systematic erosion of its state capacities and long-term destabilization, this paper examines the conceptual foundations of U.S. national security, delineates American strategic objectives in the Middle East, and analyzes the stages, instruments, and structural determinants of their implementation, while assessing their effectiveness. The study argues that U.S. strategy reflects continuity at the level of core objectives, whereas shifts occur primarily in methods and tactical approaches. It further contends that the project of a “New Middle East” entails the reconfiguration of regional identity frameworks, with Iraq constituting an initial phase in a broader process aimed at restructuring the political environment to align with American strategic interests
Keywords: The United States of America; The Middle East; National Security; Reflects Continuity; Regional Identity